Energy and Exergy Analysis of 6 MW Gas Power Plant at BOB PT. Bumi Siak Pusako - Pertamina Hulu - Mohammad Barbarosa; Awaludin Martin; Yogie Rinaldy Ginting (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2022)
BOB PT. Bumi Siak Pusako â€“ Pertamina Hulu is Indonesian Operator Company that uses gas power plant for Pekanbaru Coastal Plan (CPP) block. The 4x6 MW energy capacities must follow energy, exergy, economics analysis and environmental impacts due to COÂ² emission and exhaust gas temperature. From the analysis, the gas power plant thermal efficiency is 42.85%, exegetic efficiency is 33.22% with the largest exergy loss of 18.7 kW in combustion chamber, 7.1 kW in compressor, and 2.69 kW in gas turbine with total cost loss due to exergy destruction of 2,537.52 /hour. The cost loss value is 1362.45 /hour for compressor, 1,962.28 /hour for combustion chamber, and 212.79 /hour for gas turbine. The exhaust emission is 0.21 kg/s, forest area required to absorb pollution is 11.63 ha, exhaust heat released is 1913.51 kW. This study indicates that the analytical method carried out can be developed and applied comprehensively to generating facilities in Indonesia.